2007
DOI: 10.1186/1471-2164-8-43
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms (SNPs) distinguish Indian-origin and Chinese-origin rhesus macaques (Macaca mulatta)

Abstract: Background: Rhesus macaques serve a critical role in the study of human biomedical research. While both Indian and Chinese rhesus macaques are commonly used, genetic differences between these two subspecies affect aspects of their behavior and physiology, including response to simian immunodeficiency virus (SIV) infection. Single nucleotide polymorphisms (SNPs) can play an important role in both establishing ancestry and in identifying genes involved in complex diseases. We sequenced the 3' end of rhesus macaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 19 publications
3
67
2
Order By: Relevance
“…Only about one-third of SNPs were shared between the two geographic populations, which indicates that most variation is region-specific. Similar results were obtained in a survey of 3’ UTR sequences in a small number of macaques 37 . A study of whole genome sequences for three Indian-origin rhesus macaques found >3 million variants present in at least two of the datasets examined 33 .…”
Section: Genetic Variation Within Primate Speciessupporting
confidence: 87%
“…Only about one-third of SNPs were shared between the two geographic populations, which indicates that most variation is region-specific. Similar results were obtained in a survey of 3’ UTR sequences in a small number of macaques 37 . A study of whole genome sequences for three Indian-origin rhesus macaques found >3 million variants present in at least two of the datasets examined 33 .…”
Section: Genetic Variation Within Primate Speciessupporting
confidence: 87%
“…Another advantage of using these non-human primates is that rhesus monkeys of different geographical origin (Indian and Chinese) have been shown to be genetically different, with a number of SNPs distinguishing the two subspecies from one another [23]. Therefore, utilizing both subspecies of monkeys in carotenoid research provides a unique opportunity for studying the nutrigenomics of xanthophyll absorption, deposition, and storage/metabolism in neural tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of microsatellite (STR) markers [43], mtDNA sequence [22] and SNPs in the 3’ ends of rhesus macaque genes [3] and ENCODE regions [33] have reported higher levels of heterozygosity in Chinese than in Indian rhesus macaques. While the majority of the Indian-origin animals sampled by Hernandez et al [33] came from the Yerkes National Primate Research Center, most of the Indian-origin animals in the present study were selected from the Caribbean Primate Research Center (CPRC).…”
Section: Discussionmentioning
confidence: 99%
“…The National Center for Research Resources (NCRR) at the NIH currently sponsors six rhesus macaque Working Groups (WGs), one of which, the Genetics and Genomics WG, has assumed the stated goal of instituting uniform SNP-based genetic characterization protocols for parentage testing, ancestry determination and population genetic assessments [2]. In addition, several research groups are in the process of quantifying genomic variation in captive populations of rhesus macaques [35]. The data presented here were collected as part of a larger project to discover, quantify and validate single nucleotide polymorphisms (SNPs) in regional populations of rhesus macaques included in captive breeding populations in the US.…”
Section: Introductionmentioning
confidence: 99%